Correlation of temperature induced conformation change with optimum catalytic activity in the recombinant G/11 xylanase A from Bacillus subtilis strain 168 (1A1) - Murakami, M. T.; Arni, R. K.; Vieira, D. S.; Degreve, L.; Ruller, R.; Ward, R. J. (Elsevier B.V., 2005)
The 1.7 angstrom resolution crystal structure of recombinant family G/11 beta-1,4-xylanase (rXynA) from Bacillus subtilis 1A1 shows a jellyroll fold in which two curved P-sheets form the active-site and substrate-binding cleft. The onset of thermal denaturation of rXynA occurs at 328 K, in excellent agreement with the optimum catalytic temperature. Molecular dynamics simulations at temperatures of 298-328 K demonstrate that below the optimum temperature the thumb loop and palm domain adopt a closed conformation. However, at 328 K these two domains separate facilitating substrate access to the active-site pocket, thereby accounting for the optimum catalytic temperature of the rXynA. (c) 2005 Federation of European Biochemical Societies. Published by Elsevier B.V. All rights reserved.
Keywords: thermostable enzyme; Crystal structure; molecular dynamics